Novel role for endogenous mitochondrial formylated peptide-driven formyl peptide receptor 1 signalling in acute respiratory distress syndrome. Issue 10 (3rd May 2017) - Dorward, David A; Lucas, Christopher D; Doherty, Mary K; Chapman, Gavin B; Scholefield, Emma J; Conway Morris, Andrew; Felton, Jennifer M; Kipari, Tiina; Humphries, Duncan C; Robb, Calum T; Simpson, A John; Whitfield, Phillip D; et al.
Abstract : Background: Acute respiratory distress syndrome (ARDS) is an often fatal neutrophil-dominant lung disease. Although influenced by multiple proinflammatory mediators, identification of suitable therapeutic candidates remains elusive. We aimed to delineate the presence of mitochondrial formylated peptides in ARDS and characterise the functional importance of formyl peptide receptor 1 (FPR1) signalling in sterile lung inflammation. Methods: Mitochondrial formylated peptides were identified in bronchoalveolar lavage fluid (BALF) and serum of patients with ARDS by liquid chromatography–tandem mass spectrometry. In vitro, human neutrophils were stimulated with mitochondrial formylated peptides and their effects assessed by flow cytometry and chemotaxis assay. Mouse lung injury was induced by mitochondrial formylated peptides or hydrochloric acid. Bone marrow chimeras determined the contribution of myeloid and parenchymal FPR1 to sterile lung inflammation. Results: Mitochondrial formylated peptides were elevated in BALF and serum from patients with ARDS. These peptides drove neutrophil activation and chemotaxis through FPR1-dependent mechanisms in vitro and in vivo. In mouse lung injury, inflammation was attenuated in Fpr1−/− mice, effects recapitulated by a pharmacological FPR1 antagonist even when administered after the onset of injury. FPR1 expression was present in alveolar epithelium and chimeric mice demonstrated that both myeloid and parenchymal FPR1 contributed to lung inflammation. Conclusions: We provide the first definitive evidence of mitochondrial formylated peptides in human disease and demonstrate them to be elevated in ARDS and important in a mouse model of lung injury. This work reveals mitochondrial formylated peptide FPR1 signalling as a key driver of sterile acute lung injury and a potential therapeutic target in ARDS.